Three Faces of the Partai Demokrasi Indonesia Perjuangan in the Omnibus Law Policy of the Job Creation Law - Agra Septian Pravito; Ahmad Zaki Fadlur Rohman (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
Indonesia’s contemporary political landscape is deeply shaped by the pivotal role of political parties in the formulation of public policy. As the ruling party with one of the largest grassroots constituencies, the Indonesian Democratic Party of Struggle (PDI-Perjuangan) holds a decisive influence in legislative decision-making. Katz and Peter Mair. These three faces include: the party in public office, the party on the ground, and the party central office. The research employs a qualitative method with a case study approach, based on interviews with party representatives as well as an analysis of documents, news sources, and academic literature. The research was conducted at the PDIP Branch Leadership Councils located in Depok, Tangerang, and East Jakarta. Data were collected through in-depth interviews with key informants and supported by relevant documentation analysis. The findings reveal a clear discrepancy between PDI-Perjuangan’s ideological commitment to public welfare and its parliamentary faction’s support for the Job Creation Law. This contradiction has sparked disappointment among labour groups and party sympathizers. By analyzing the party's three faces, this study uncovers internal tensions which are legislative elites prioritize political pragmatism, the central office struggles to balance control and coherence, while grassroots cadres resist policies seen as betraying party ideals. The study demonstrates that PDI-Perjuangan’s political decisions are shaped by government pressure, economic interests, and internal fragmentation. Ultimately, the research highlights the ongoing dilemma between upholding party idealism and pursuing strategic political compromise in Indonesia’s legislative process.